2016
DOI: 10.1038/nature18935
|View full text |Cite
|
Sign up to set email alerts
|

CD47-blocking antibodies restore phagocytosis and prevent atherosclerosis

Abstract: Summary Atherosclerosis is the disease process underlying heart attack and stroke1. Advanced lesions at risk for rupture are characterized by the pathological accumulation of diseased vascular cells and apoptotic cellular debris2. Why these cells are not cleared remains unknown3. Here we show that atherogenesis is associated with upregulation of CD47, a key ‘don’t eat me’ molecule known to render malignant cells resistant to programmed cell removal (PrCR), or ‘efferocytosis’4–7. We find that administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
518
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 512 publications
(534 citation statements)
references
References 41 publications
11
518
1
4
Order By: Relevance
“…Data from human and mouse studies suggest that plaque necrosis results from 2 complementary processes, postapoptotic necrosis secondary to defective efferocytosis as examined here (2, 3) and a primary cell necrosis process called necroptosis (27,28). While the current study is focused on an efferocytosis defect in phagocytes themselves, a recent study showed that some apoptotic cells in human and mouse lesions inappropriately retain CD47, which blocks their engulfment by normal phagocytes (29). Interestingly, oxLDL, which was shown here to promote MerTK cleavage and defective efferocytosis, can induce necroptosis in macrophages, and these cells are also poorly Two such proteins, TGF-β1 and IL-10, were significantly increased in Mertk CR plasma (Supplemental Figure 6A).…”
Section: Resultsmentioning
confidence: 94%
“…Data from human and mouse studies suggest that plaque necrosis results from 2 complementary processes, postapoptotic necrosis secondary to defective efferocytosis as examined here (2, 3) and a primary cell necrosis process called necroptosis (27,28). While the current study is focused on an efferocytosis defect in phagocytes themselves, a recent study showed that some apoptotic cells in human and mouse lesions inappropriately retain CD47, which blocks their engulfment by normal phagocytes (29). Interestingly, oxLDL, which was shown here to promote MerTK cleavage and defective efferocytosis, can induce necroptosis in macrophages, and these cells are also poorly Two such proteins, TGF-β1 and IL-10, were significantly increased in Mertk CR plasma (Supplemental Figure 6A).…”
Section: Resultsmentioning
confidence: 94%
“…We showed that fibrogenic cells expressed high levels of the self-protective don't-eat-me epitope CD47. It had been shown in various solid cancers and hematopoietic malignancies, and most recently in atherosclerosis, that blockade of CD47 by antibodies or artificial, high-affinity Sirpα analogs prevents this repressive signal in macrophages, leading to their activation and active phagocytosis (24). The remarkable low toxicity of anti-CD47 treatments, however, suggested that additional alterations in cancer cells are required to induce phagocytosis (21,25).…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Recently, increased antiphagocytic CD47 on the surface of plaque cells and loss of surface Mer tyrosine kinase on plaque phagocytes have been shown to play important roles in mouse and human atherosclerosis. 61,62 These defects lead to secondary necrosis, making cells and oxLDL debris recognizable to anti-MDA and anti-phosphorylcholine antibodies. These antibodies provide an alternate protective layer that is nevertheless insufficient to prevent atherosclerosis progression; however, the lack of such antibodies greatly accelerates plaque growth.…”
mentioning
confidence: 99%